2023
DOI: 10.1007/s11869-023-01447-5
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of health impact assessments of PM2.5 from South African coal-fired power stations

Siyabonga P. Simelane,
Kristy E. Langerman

Abstract: Unabated emissions of precursor gases from coal-fired power stations in South Africa greatly contribute to ambient PM2.5 concentration in the region, but estimates of the number of associated premature mortalities vary vastly. The application of the exposure-response function is one of the reasons for the differences in estimates of premature mortalities; since the relationship between mortality and PM2.5 exposure flattens out at higher PM2.5 concentrations, a smaller number of premature mortalities is calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The study found that emissions from coal-fired power stations contribute between 1.8% and 5.6% of all deaths attributable to PM 2.5 exposure in the study area identified (RSA as a whole, in areas affected by PM 2.5 from power stations). They also found that coal-fired power station emissions contribute to a relatively higher proportion of premature deaths where power stations have the highest contribution to ambient PM 2.5 concentrations (Simelane and Langerman 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study found that emissions from coal-fired power stations contribute between 1.8% and 5.6% of all deaths attributable to PM 2.5 exposure in the study area identified (RSA as a whole, in areas affected by PM 2.5 from power stations). They also found that coal-fired power station emissions contribute to a relatively higher proportion of premature deaths where power stations have the highest contribution to ambient PM 2.5 concentrations (Simelane and Langerman 2020).…”
Section: Discussionmentioning
confidence: 95%
“…their associated health risks on human health (Simelane and Langerman 2020). District municipality-level population data were used to derive population-weighted PM 2.5 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews focused on the impact of air pollutants from coal combustion on human health in high-income countries 24 25. Few studies have investigated the health effects of air pollution in areas where CFPPs are located among children and adults particularly in low/middle-income countries 10 26–29. These were epidemiological observational studies with either an ecologic or cross-sectional study design.…”
Section: Introductionmentioning
confidence: 99%